2021
DOI: 10.1136/jnnp-2020-325497
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous distribution of tau pathology in the behavioural variant of Alzheimer’s disease

Abstract: ObjectiveThe clinical phenotype of the rare behavioural variant of Alzheimer’s disease (bvAD) is insufficiently understood. Given the strong clinico-anatomical correlations of tau pathology in AD, we investigated the distribution of tau deposits in bvAD, in-vivo and ex-vivo, using positron emission tomography (PET) and postmortem examination.MethodsFor the tau PET study, seven amyloid-β positive bvAD patients underwent [18F]flortaucipir or [18F]RO948 PET. We converted tau PET uptake values into standardised (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
2
18
1
Order By: Relevance
“…In line with amyloid and tau PET findings, the meta-analyses on neuropathological data showed that bvAD and tAD did not differ in the neuropathological burden of amyloid-β (3 studies; 20 participants) across frontal regions (SMD, 0.23 [95% CI, −0.36 to 0.81]; P = .45), medial temporal lobe (SMD, −0.06 [95% CI, −0.65 to 0.53]; P = .84), or occipital cortex (SMD, −0.16 [95% CI, −1.05 to 0.73]; P = .73; eFigure 7 in the Supplement). Furthermore, there was no difference in tau burden (4 studies; 28 participants) across frontal regions (SMD, −0.05 [95% CI, −0.56 to 0.46]; P = .84), medial temporal lobe (SMD, 0.32 [95% CI, −0.19 to 0.83]; P = .22), or occipital cortex (SMD, −0.36 [95% CI, −0.95 to 0.23]; P = .24; eFigure 7 in the Supplement).…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…In line with amyloid and tau PET findings, the meta-analyses on neuropathological data showed that bvAD and tAD did not differ in the neuropathological burden of amyloid-β (3 studies; 20 participants) across frontal regions (SMD, 0.23 [95% CI, −0.36 to 0.81]; P = .45), medial temporal lobe (SMD, −0.06 [95% CI, −0.65 to 0.53]; P = .84), or occipital cortex (SMD, −0.16 [95% CI, −1.05 to 0.73]; P = .73; eFigure 7 in the Supplement). Furthermore, there was no difference in tau burden (4 studies; 28 participants) across frontal regions (SMD, −0.05 [95% CI, −0.56 to 0.46]; P = .84), medial temporal lobe (SMD, 0.32 [95% CI, −0.19 to 0.83]; P = .22), or occipital cortex (SMD, −0.36 [95% CI, −0.95 to 0.23]; P = .24; eFigure 7 in the Supplement).…”
Section: Resultsmentioning
confidence: 54%
“…The systematic literature search yielded 1257 records, of which 116 studies were assessed at full-text level for eligibility and 83 studies met inclusion criteria (eFigure 5 in the Supplement for flowchart). Confirmation of AD pathology was present in 91.1% of cases with bvAD based on autopsy data (36 studies; n = 334), genetic data (9 studies; n = 21), or biomarker data (31 studies; n = 262), while no information was available in 9.9% of cases (11 studies including 68 cases of bvAD). Thirteen studies were eligible for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a better predictor of the severity of symptoms (especially cognition decline) and neuronal loss than amyloid beta peptide [3,98]. Intriguingly, patterns of brain atrophy implied by tau deposits can precede and be identical to later detection by MRI and FDG-PET [99,100]. Meanwhile, different AD phenotypes show higher NFT burden in specific brain regions.…”
Section: R and 4r Tauopathymentioning
confidence: 99%
“…Today, factors modulating the clinical course of pathology are still poorly understood. Several studies have outlined that tau pathology is associated with the heterogeneity of disease evolution [30], although this is not reported in all studies [31,32]. Modulation of Aβ structures is another potential culprit to explain different fate of AD evolution in particular to explain rapidly progressive forms of AD [33].…”
Section: Clinical Fate In Alzheimer'smentioning
confidence: 99%